Long-Term Relapse Outcomes of Smoking Cessation in Older Smokers - Didem Gorgun Hattatoglu; Birsen Pinar Yildiz (Haseki Tıp Bülteni, 2021)

(untitled)
Aim:Limited data are available in the literature about the long-term results of smoking cessation and the relapse rate in older smokers. We aimed to demonstrate the efficacy of short- and long-term smoking cessation behaviors in individuals over 65 years of age.Methods:Patients’ data were analyzed retrospectively from hospital records between 2014 and 2018. All patients received individual behavioral therapy and were prescribed the drugs that were best suited for their individual circumstances, such as nicotine replacement therapy, bupropion, and varenicline. Patients who quit smoking during the three-month period of outpatient follow-up were contacted by phone at least two years later and asked whether they still smoked or not.Results:In total, 68 older participants (13 female and 56 male) were included. In the initial three-month follow-up period, 29 of the participants (42.6%) dropped out of the smoking cessation program after the first interview. Eleven of the smokers (16.2%) did not quit smoking, and 28 (41.1%) did quit smoking. Fourteen participants (20.6%) achieved long-term abstinence (i.e., were not smoking at the two-year follow-up), while the remaining 10 participants (14.7%) had started to smoke again. No statistically significant difference was found between quitters and non-quitters in terms of age, gender, duration of the smoking habit, the number of cigarettes smoked daily, the reason for starting smoking, the reason for the desire to quit smoking, and the treatment methods used.Conclusion:Smoking cessation strategies should be tailored and constantly re-evaluated in elderly people for safe management, and they should be followed up closely to avoid relapse risk.